Rohingya refugee–host community conflicts in Bangladesh: issues and insights from the "field". Issue 3 (3rd April 2023) - Habib, Md Reza
ABSTRACT: Despite being a resource-scarce country, Bangladesh hosts a million Rohingya refugees on humanitarian grounds and offers them protection, and shelter. How does their presence affect the provision of resources, services, and access for both residents and refugees? I analyze the conflict and competition over limited resources. I argue that the arrival of the Rohingyas has caused significant distress to the host community in Cox's Bazar district, but there is an inadequate reflection on their distress. By examining the locals' relationships with the refugees through field engagements, I argue their presence leads to conflict, in three main areas: public service provision, economic resources, and environmental resources.